The Genesis of a Thin-Bedded Beach-Bar System Under the Strike-Slip Extensional Tectonic Framework: A Case Study in the Bohai Bay Basin - Jing Wang; Youbin He; Hua Li; Bin Feng; Zhongxiang Zhao; Xing Yu; Xiangyang Hou (Applied Sciences)
The lower sub-member of Member 2, Dongying Formation (Paleogene) in the HHK Depression hosts an extensively developed thin-bedded beach-bar system characterized by favorable source rock conditions and reservoir properties, indicating significant hydrocarbon exploration potential. Integrating drilling cores, wireline log interpretations, three-dimensional seismic data, geochemical analyses, and palynological data, this study investigates the sedimentary characteristics, sandbody distribution patterns, controlling factors, and genetic model of this lacustrine beach-bar system. Results reveal the following: (1) widespread thin-bedded beach-bar sandbodies dominated by fine-grained sandstones and siltstones, exhibiting wave ripples and low-angle cross-bedding; (2) two vertical stacking patterns, Type A, thick mudstone intervals intercalated with laterally continuous thin sandstone layers, and Type B, composite sandstones comprising thick sandstone units overlain by thin sandstone beds, both demonstrating significant lateral continuity; (3) three identified microfacies: bar-core, beach-core, and beach-margin facies; (4) key controls on sandbody development: paleoenvironmental evolution establishing the depositional framework, secondary fluctuations modulating depositional processes, strike-slip extensional tectonics governing structural zonation, paleobathymetry variations and paleotopography controlling distribution loci, and provenance clastic influx regulating scale and enrichment (confirmed by detrital zircon U-Pb dating documenting a dual provenance system). Collectively, these findings establish a sedimentary model for a thin-bedded beach-bar system under the strike-slip extensional tectonic framework.